Analysis of bell pepper (Capsicum annuum) cultivation in response to fertigation and training systems under protected environment - KUMAR, SANJEEV; PATEL, N B; SARAVAIYA, S N (The Indian Journal of Agricultural Sciences, 2018)
The experiment was carried out to standardize fertigation and training system for bell pepper (Capsicum annuum L.) cultivation under protected conditions during 2013-14, 2014-15, 2015-16 involving 4 levels of fertilizer [F1-300:300:300 kg/ha (RDF through conventional method), F2-300:300:300 kg/ha (Fertigation), F3-250:250:250 kg/ha (Fertigation), F4-350: 350: 350 kg/ha (Fertigation)] and 3 training systems (P1-Two shoot system, P2-Three, P3-Four). The results revealed significant effect on plant height and fruit length due to main effect of fertilizers recordingmaximum values for the traits in F4 level. F3 level of fertilizers contributed towards earliness and maximum fruit diameter (7.31 cm), pericarp thickness (0.70 cm), fruit weight (150.40 g), fruit volume (236.31 cc), number of fruits (20.78), yield per plant (3.11 kg) and yield per 1000 m2 (8.90 t). P1 level of training system excelled all other training systems exhibiting maximum plant height during different periodical observations at 30, 60, 90 and 120 days after planting (DAP). The plants trained to P3 level were observed to earliest in flowering as well as picking and producedsignificantly maximum number of fruits (21.09), fruit yield per plant (2.62 kg) and yield per 1000 m2 (7.99 t). P1 training system showed significant effect on various fruit parameters and recorded maximum fruit length, diameter, pericarp thickness, fruit weight, fruit volume, shelf life. Treatment combination F4P1 displayed significantly maximum plant height of 147.34 cm at 90 DAP. Bell pepper plants fertigated with F3 level and trained to P3 system (F3P3) recorded maximum number of fruits per plant (25.79), fruit yield per plant (3.63) and fruit yield per 1000 m2 (10.74) thereby revealing higher net returns of Rupees 8621 with BCR of 1.10 for bell pepper.